Representation of Masculinity in the Hugo Boss Perfume Advertisement on Youtube.com - La Ode Abdul Handoko Marzuki; Neil Amstrong; Arman Arman (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study focuses on masculinity through power, image, ideal, and domination based on Connel’s masculinity theory displaying the symbol of masculinity in the Hugo Boss perfume advertisement. The Objective of the study in this research is to describe the representation of masculinity which is depicted in the Hugo Boss perfume advertisement on Youtube.com. The research method that the author uses is qualitative. The data source for this research is Hugo's perfume ad videos on YouTube. The data collection method used is proficient free listening and note-taking techniques. This method is used to remember that the data used is pausing and screenshotting the advertisement. As a result, there are 20 pieces of data found by a researcher from 5 advertisements that the researcher chose as the object. The researcher found that there is a unique new concept of masculinity or appearance in Hugo Boss perfume advertisements, the representation of masculinity in the Hugo Boss advertisement is divided into power, image, ideal, and dominance. Hugo Boss perfume advertisements continue to reinforce the ideology of masculinity where masculinity is the separation between men and women in terms of gender and masculinity represents the male gender. The strengthening of masculinity ideology in this advertisement is shown in the aspect of men who are macho and successful. This advertisement also dismantles the ideology of masculinity in the aspect of men having a nerd appearance and manipulative attitudes towards women, both of which are not stereotypical.